Generation of Electricity by Using Microbial Fuel Cell Prototype Fed by Sewage: Case Study at the University of Dar es Salaam - Said, Mahir M; Saad, Asia A; John, Geoffrey R; Mushi, Aviti T (Tanzania Journal of Science, 2023)
The access to electricity is still not reliable in Tanzania. Whilst, there are several locations within the country that have wastewater cites that are not economically used to produce electricity. At the University of Dar es Salaam (UDSM), there are main grid power, and few scattered solar panels. This study was intended to bridge the divide between the current increasing power demands of the UDSM by exploiting not so much used sources, such as electric energy from wastewater. This study was undertaken to develop a Microbial Fuel Cell (MFC) prototype fed by sewage in Dar es Salaam, for electricity generation using cost effective materials for the cathode compartment. The collection of samples took place using sewage substrates from the UDSM oxidation ponds. The untreated sewage was collected from oxidation ponds. Preliminary experiments were carried out to identify the cathode and substrate that produced better results in terms of volts and current output. Aluminium produced the most desirable results compared to copper, stainless steel and mild steel in all the substrates. On the other hand, untreated sewage with aluminium/carbon electrodes produced higher voltage and current compared to treated sewage with the same electrodes. Thereafter, a prototype of the MFC was developed by connecting three single chambered cells in series of 628 cm3 volume of untreated sewage with aluminium and carbon electrodes. The prototype generated a stable voltage of 1.73 V and a current of 0.07 mA recorded for a period of one hour. The power generated was enough to light a 6.25 mW LED bulb of 25 mA across a 100 Ω resister. Therefore, untreated sewage produced more power in MFCs with aluminium/carbon electrodes compared to the other tested materials. Keywords: Aluminium electrodes, charcoal electrode, alternative energy source, wastewater